2012
DOI: 10.1136/jclinpath-2011-200340
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous subtype as prognostic factor in colorectal cancer: a systematic review and meta-analysis

Abstract: MAC more often originates from the right colon and is less frequent in male subjects. The authors did not identify a difference in the proportion of stage IV patients at presentation. Mucinous differentiation results in a 2-8% increased hazard of death, which persists after correction for stage. More research is needed to define the interaction between mucinous differentiation, MSI and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
206
4
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(238 citation statements)
references
References 72 publications
21
206
4
7
Order By: Relevance
“…In another study conducted by Kanemistu et al [22], MA patients with either complete or incomplete surgical resection had worse outcomes compared to non-mucinous types. Moreover, MA was associated with a 2–8% increase in risk of death in Verhulst et al’s meta-analysis [23].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In another study conducted by Kanemistu et al [22], MA patients with either complete or incomplete surgical resection had worse outcomes compared to non-mucinous types. Moreover, MA was associated with a 2–8% increase in risk of death in Verhulst et al’s meta-analysis [23].…”
Section: Discussionmentioning
confidence: 92%
“…Of note, patients with colonic MA tend to be younger, tend to present with advanced stage, and more likely to have right-sided tumors, peritoneal metastasis, and incomplete resection of the colonic tumor [22,23,26,27]. Microsatellite instability (MSI) of more than 40% frequently occurs in right-sided colonic cancer and carries better prognostic outcomes compared to microsatellite stable (MSS) tumors [11,26].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of mucinous cancers of the colon and rectum showed a worse prognosis for mucinous cancers compared with nonmucinous types, even when corrected for stage at presentation [10]. Previously, suggestions had been made that any difference in clinical outcomes between mucinous and nonmucinous carcinomas were attributed to a more advanced stage at presentation.…”
Section: Clinical Outcomes and Survivalmentioning
confidence: 99%
“…One of the largest studies examining the outcomes of mucinous tumours investigated 16,991 patients and found that just over 18 % of all mucinous tumours were found in the rectum compared with 29 % of non-mucinous tumours [9]. A recent meta-analysis of outcomes in mucinous colon cancer, which included some studies with rectal tumours, reported that mucinous tumours were more frequently found proximal to the splenic flexure compared to non-mucinous adenocarcinoma [10]. Conversely, mucinous tumours are more common than non-mucinous in the proximal colon.…”
Section: Epidemiology and Clinical Characteristicsmentioning
confidence: 99%
“…Some studies believed that mucinous histologic type itself is an important prognostic factor affecting the progression of tumor and outcome of patients with colorectal carcinoma. And the survival rate of patients with mucinous adenocarcinoma could be inferior to the patients with non-mucinous adenocarcinoma (NMC) (Kanemitsu et al, 2003;Verhulst et al, 2012;Biffi et al, 2013;Hugen et al, 2013), while some other studies did not find any adverse prognostic effect (Leopoldo et al, 2007;Farhat et al, 2008;Xie et al, 2009;Langner et al, 2012;Yamaguchi et al, 2012).…”
Section: Rectal Carcinoma Patientsmentioning
confidence: 99%